2022
DOI: 10.1177/17589983221120839
|View full text |Cite
|
Sign up to set email alerts
|

Brief psychological screening for trapeziectomy: Identifying patients at high risk of a poor functional outcome

Abstract: Introduction: This study investigates if the psychological subscale from the STarT Back Screening Tool (STarT Psych-sub) identifies patients at high risk of a poor functional outcome after a trapeziectomy based on modifiable psychological factors. Methods: A total of 83 patients completed the STarT Psych-sub, QuickDASH (Quick Disabilities of the Arm, Shoulder and Hand), Patient Evaluation Measure (PEM) and a numeric pain rating scale (NPRS) before trapeziectomy. QuickDASH, PEM and NPRS were completed at 6 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The STarT Back tool was developed to screen primary care patients with low back pain for prognostic indicators relevant to providing personalized care. However, the measure was recently investigated in patients undergoing trapeziectomy surgery and identified a subgroup of patients at ‘high-risk’ who reported significantly worse outcomes(28). Given the growing evidence that higher levels of anxiety (29, 30) and catastrophic thinking in relation to pain (29, 31) are associated with poorer hand surgery outcome, validation of brief psychological screening tools is an important step in personalized medicine.…”
Section: Methodsmentioning
confidence: 99%
“…The STarT Back tool was developed to screen primary care patients with low back pain for prognostic indicators relevant to providing personalized care. However, the measure was recently investigated in patients undergoing trapeziectomy surgery and identified a subgroup of patients at ‘high-risk’ who reported significantly worse outcomes(28). Given the growing evidence that higher levels of anxiety (29, 30) and catastrophic thinking in relation to pain (29, 31) are associated with poorer hand surgery outcome, validation of brief psychological screening tools is an important step in personalized medicine.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study found 29% of patients who accepted an offer of trapeziectomy for trapeziometacarpal arthritis presented with notable opportunities for improving symptoms of anxiety and depression, and unhelpful catastrophic thinking and kinesiophobia (Larson et al., 2022). Although patients experienced a similar magnitude of improvement in comfort and capability 1 year after surgery, the final result was correlated with mindset.…”
Section: Ways In Which Mental Health Manifests In Upper Limb Speciali...mentioning
confidence: 99%